Building Creativity in Students’ Spatial Thinking Skills using ArcGIS Story Maps - Wisang Elang Fajar Nisnala; Purwanto Purwanto; Didik Taryana (Universitas Pendidikan Indonesia, 2023)
Knowledge of spatial concepts, the process of reasoning, and the use of representational tools are characteristics of cognitive skills from spatial thinking abilities that students should master. This study aims to determine the effect of using ArcGIS Story maps in collaboration with a challenge-based learning model on the creativity of students' spatial thinking skills. Quasi Experiment with a quantitative approach is a research method used in research. The subjects of the research analysis were high school students, with 68 students consisting of two homogeneous classes. The creative essay test of spatial thinking ability and questionnaire were chosen as data collection techniques. And data analysis using a t-test. Statistical tests prove that using ArcGIS Story maps affects the creativity of spatial thinking skills manifested in the mastery of spatial perception, spatial visualization, spatial relations, spatial orientation, and mental rotation, which increases students' posttest scores. Meanwhile, there are inconsistencies in the skills of using ArcGIS Story maps with posttest scores.